Mild clinical phenotype and subtle radiographic findings in an infant with cartilage-hair hypoplasia - Türkkani-Asal, Gülten; Alanay, Yasemin; Turul-Ozgür, Tuba; Zenker, Martin; Thiel, Christian; Rauch, Anita; Unal, Sule; Gürgey, Aytemiz; Tezcan, Ilhan (The Turkish Journal of Pediatrics, 2009)
Cartilage-hair hypoplasia (CHH) is one of the well-known immuno-osseous dysplasias (IOD), which are a combination of skeletal dysplasia and immunodeficiency. It is characterized by disproportionate short stature, fine sparse hair, ligamentous laxity, hematological abnormalities with anemia, a predisposition to malignant tumors, and recurrent infections usually due to cellular and/or humoral immunodeficiency. However, there is a significant overlap of clinical findings among the other IODS such as Schimke’s IOD. Here, we present a case of CHH with mild skeletal changes and immunological findings associated with recurrent otitis media, neutropenia, and lymphopenia. With this report, we once more emphasize the difficulty in assessing young individuals with CHH presenting with mild ectodermal findings and subtle radiographic changes.